The effect of chloroquine on cervical cancer via the PI3K/AKT/MDM2 pathway - Dandan Xu; Chenyang Hou; Jianliang Chang; Shuaibo Yang; Zhicong Yang; Zelong Yuan; Jingqi Li; Shuqin Liu; Yaqun Liu; Yingpeng Su; Peng Gao; Xiaojuan Liu (Discover Oncology)
Abstract Background Cervical cancer (CC), the most prevalent malignant tumor in the female reproductive system, is characterized by its high incidence and mortality rates. Chloroquine(CQ), a 4-aminoquinoline drug originally used to prevent and treat malaria, has gained recognition as an adjuvant anti-cancer agent. However, whether chloroquine exhibits anti-CC activity and its underlying mechanisms remain unclear. This study aimed to elucidate chloroquine’s anti-cancer effects, focusing on the PI3K/AKT/MDM2 pathway, by integrating network pharmacology and in vitro experiments. Methods Firstly, CQ and its associated targets related to cervical cancer were identified using the PharmMapper, SwissTargetPrediction, DrugBank, GeneCards, and DisGeNET databases. A protein–protein interaction (PPI) network was constructed to screen for key targets. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted to predict the underlying biological functions and mechanisms involved in the anti-colorectal cancer effects of CQ. Subsequently, CCK-8, colony formation, and wound-healing assays were performed to assess the impact of CQ treatment on the proliferation ability of HeLa cells. Cell apoptosis was analyzed using flow cytometry, and the expression of apoptosis-related proteins was determined through Western blotting. Finally, the effects of CQ on the PI3K/AKT/MDM2 signaling pathway were evaluated via Western blotting. Results A total of 7,846 potential treatment targets for CQ were identified, among which 126 were related to CC. Through PPI network analysis of 100 common targets, eight core targets were identified: TNF, MDM2, SLC6A4, GRIN1, CHRM1, EZH2, ACHE, and ADRB2. KEGG enrichment analysis revealed the PI3K/AKT signaling pathway as a central pathway of interest. Various concentrations of CQ (25, 50, and 75 µM) inhibited the viability of HeLa cells while showing no significant effect on H8 cells. Following treatment with CQ (25 µM and 75 µM), a reduction in proliferation and colony formation was observed in HeLa cells. Furthermore, CQ treatment led to an increase in the expression of apoptosis-related proteins (Bax, Bcl-2, cleaved-PARP) and a decrease in the expression of proteins associated with the PI3K/AKT/MDM2 signaling pathway (p-PI3K, p-AKT, and p-MDM2). Conclusions This study suggests that chloroquine may induce apoptosis by inhibiting the PI3K/AKT/MDM2 signalling pathway.